Human Rhinovirus VPg Uridylylation AlphaScreen for High-Throughput Screening. (February 2014) - Gingras, Rock; Mekhssian, Kevork; Fenwick, Craig; White, Peter W.; Thibeault, Diane
As an obligate step for picornaviruses to replicate their genome, the small viral peptide VPg must first be specifically conjugated with uridine nucleotides at a conserved tyrosine hydroxyl group. The resulting VPg-pUpU serves as the primer for genome replication. The uridylylation reaction requires the coordinated activity of many components, including the viral polymerase, a conserved internal RNA stem loop structure, and additional viral proteins. Formation of this complex and the resulting conjugation reaction catalyzed by the polymerase, offers a number of biochemical targets for inhibition of an essential process in the viral life cycle. Therefore, an assay recapitulating uridylylation would provide multiple opportunities for discovering potential antiviral agents. Our goal was to identify inhibitors of human rhinovirus (HRV) VPg uridylylation, which might ultimately be useful to reduce or prevent HRV-induced lower airway immunologic inflammatory responses, a major cause of asthma and chronic obstructive pulmonary disease exacerbations. We have reconstituted the complex uridylylation reaction in an AlphaScreen suitable for high-throughput screening, in which a rabbit polyclonal antiserum specific for uridylylated VPg serves as a key reagent. Assay results were validated by quantitative mass spectrometric detection of uridylylation.